Islamic finance in a nutshell : a guide for non-specialists - Kettell, Brian (Wiley finance series, 2010)
An increased interest in Islamic finance is related to the capital market crises, ethical policies, and banks. Islamic Finance in a Nutshell provides the fundamentals of Islamic finance, like sharia's law